The Optimum Calcium Concentration for Seedling Growth of Mongolian Pine (Pinus Sylvestris Var. Mongolica) Under Different Soil Types in Northern Semi-Arid Areas of China - Li, Hui; Li, Xiangjun; Zhang, Guangqi; Weng, Xiaohang; Huang, Shenglan; Zhou, Yongbin; Zhang, Songzhu; Liu, Liying; Pei, Jiubo (Frontiers in Environmental Science, 2022)
Mongolian pine, as one of the major tree species of the Three-North Shelterbelt Project in the northern semiarid region of China, is very important for ensuring ecological and environmental security. Ca, as an imperative mineral element for plant development and a second messenger, partakes in photosynthesis and affects the growth of plants. However, the optimal calcium concentration for its growth in different soil types is still unclear. In this study, fifteen treatments with combinations of three different soils (e.g., sandy soil, cinnamon soil, dark brown soil) and five calcium concentration gradients (e.g., 0, 100, 200, 400, and 800 mg∙kg-1) were conducted to investigate this effect by measuring the indices of growth, biomass, photosynthetic pigment, gas exchange rate, photosynthates, chlorophyll fluorescence parameters and water use efficiency (iWUE) based on a pot experiment. The results showed that the optimal calcium concentration of Mongolian pine seedlings in sandy soil and cinnamon soil was 0–100 mg∙kg-1, and the optimal calcium concentration of Mongolian pine seedlings in dark brown soil was 100–200 mg∙kg-1. In other words, the results showed that there was an optimal calcium concentration for the growth of Mongolian pine seedlings, and the optimal calcium concentration was different under different soil types. And if the calcium concentration in the soil was too high, it would have an inhibitory effect on Mongolian pine seedlings, low calcium concentration maybe don’t work. The addition of an appropriate amount of exogenous calcium could promote the growth of Mongolian pine seedlings in different soil types. The plant height, basal diameter and biomass of Mongolian pine seedlings all increased significantly after applying an appropriate amount of calcium (p < 0.05); the addition of an appropriate amount of exogenous calcium could promote the photosynthetic characteristics of Mongolian pine seedlings in different soil types. Under sandy soil and cinnamon soil, the peaks for Pn, Gs, Tr, accumulation of soluble sugar and starch of Mongolian pine seedlings occurred at 0–100 mg∙kg-1, and the decreasing trend of the Fv/Fm value was significant in the case of exceeding 200 mg∙kg-1 (p < 0.05), indicating that the growth of Mongolian pine seedlings was affected when calcium concentrations higher than 200 mg∙kg-1 were applied. Moreover, under dark brown soil, the peaks for Pn, Gs, Tr, and accumulation of soluble sugar and starch of Mongolian pine seedlings occurred at 100–200 mg∙kg-1; similarly, the growth of Mongolian pine seedlings was affected when calcium concentrations higher than 200 mg∙kg-1 were applied. Compared with the treatment without calcium, after applying an appropriate amount of exogenous calcium, the water use efficiency of Mongolian pine seedlings in different soil types was significantly improved, though it was significantly reduced at 800 mg∙kg-1 (p < 0.05).